2019
DOI: 10.1148/radiol.2019181883
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Flexible 12-Channel Screen-printed Pediatric MRI Coil

Abstract: ediatric MRI is often performed with heavy, large, and relatively inflexible coil arrays designed and built for adult MRI. For awake children, these arrays can be intimidating and uncomfortable, thereby restricting the child's breathing. For parents, they contribute to the stress of the examination. For pediatric caregivers, the coils complicate the placement of medical support equipment, such as mechanical ventilation tubes, pulse oximeters, anesthetic lines, respiratory bellows, blood pressure cuffs, electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…Further improvement in flexibility was reached with printed and stitched coils on flexible substrate or even elastic textile. Screen-printed MRI coils [17] developed by Corea et al have shown to be a reliable alternative to bulky conventional coils with comparable SNR, suitable especially for pediatric imaging [18]. Stretchable Rx coils produced with copper braids [19], [20], meandered conductors [21], liquid metal printed into neoprene support material [22], liquid metal filled tubes [23], [24] or conductive elastomers [25] mostly target wrist or knee imaging and offer a truly wearable solution.…”
Section: Introductionmentioning
confidence: 99%
“…Further improvement in flexibility was reached with printed and stitched coils on flexible substrate or even elastic textile. Screen-printed MRI coils [17] developed by Corea et al have shown to be a reliable alternative to bulky conventional coils with comparable SNR, suitable especially for pediatric imaging [18]. Stretchable Rx coils produced with copper braids [19], [20], meandered conductors [21], liquid metal printed into neoprene support material [22], liquid metal filled tubes [23], [24] or conductive elastomers [25] mostly target wrist or knee imaging and offer a truly wearable solution.…”
Section: Introductionmentioning
confidence: 99%
“…Both TE and TR (TE=80110μs, TR=3.13.7ms) increased compared to adult studies due to smaller FOV and excitation slab. The number of spokes was adjusted between 80 thousand to 90 thousand to keep the total scan time no more than 5 min 30 s. Due to varied scan subject size, different receiver coil arrays were used in pediatric scans to improve SNR: 8‐channel and 32‐channel cardiac arrays (GE Healthcare, Waukesha, WI), as well as a 12‐channel flexible screen‐printed coil array (Inkspace Inc., Moraga, CA) …”
Section: Methodsmentioning
confidence: 99%
“…Parallel imaging acceleration is routinely used clinically to accelerate MR acquisition by not sampling some lines of k-space in the phase-encoding direction while estimating missing information from coil sensitivity profiles of adjacent receiver elements. Parallel imaging usually leads to 2- to 3-fold acceleration, although recently developed high channel count and flexible coils offer the promise of higher acceleration factors and are undergoing clinical validation for applications in the pediatric population [ 49 , 50 ]. Higher signal acquired with a 3-tesla (T) versus a 1.5-T scanner, combined with parallel imaging, has the potential to reduce the overall scan time and thus the need for sedation/general anesthesia.…”
Section: Strategies To Mitigate Sedation and Anesthesia Risksmentioning
confidence: 99%